A review of laws for sustainable environmental management in the Nigerian oil and gas sector (2014)
This paper analyses the laws that aim to control the use of the environment by the stake holders in the oil and gas sector of Nigeria, with a view to ensuring that the goals of sustainable development are achieved in the use of the environment. It analytically examines the constitution and various legislation and some regulations that provide for the protection of the environment from oil pollution directly or by implication. It adopts the method of indepth content analysis of the relevant laws on oil and gas in Nigeria. The paper is in five parts starting with the introduction, followed by the second part on concept clarification. The third part of the paper is the fulcrum, analyzing the laws while part four discusses the importance of enforcement being the link between the law and reality. The paper concludes in part five and recommends law reform, better enforcement, and stiffer penalties for violators and exploitation of technology for better environmental management.